FTO gene SNPs associated with extreme obesity in cases, controls and extremely discordant sister pairs - R. Arlen Price; Weidong Li; Hongyu Zhao (2008)
FTO is a gene located in chromosome region 16q12.2. Recently two studies have found associations of several single nucleotide polymorphisms (SNPs) in FTO with body mass index (BMI) and obesity, particularly rs1421085, rs17817449, and rs9939609. We examined these three SNPs in 583 extremely obese women with current BMI greater than 35 kg/m2 and lifetime BMI greater than 40 kg/m2, and 544 controls who were currently normal weight (BMI<25 kg/m2) and had never been overweight during their lifetimes. We detected highly significant associations of obesity with alleles in all three SNPs (p < 10-9). The strongest association was with rs1421085 (p = 3.04 × 10-10, OR = 1.75, CI = 1.47–2.08). A subset of 99 cases had extremely discordant sisters with BMI<25 kg/m2. The discordant sisters differed in allele and genotype frequencies in parallel with the overall case and control sample. The strongest association was with rs17817449 (z = 3.57, p = 3.6 × 10-4). These results suggest common variability in FTO is associated with increased obesity risk or resistance and may in part account for differences between closely related individuals.